en.wikipedia.org

Quotient rule - Wikipedia

From Wikipedia, the free encyclopedia

In calculus, the quotient rule is a method of finding the derivative of a function that is the ratio of two differentiable functions. Let {\displaystyle h(x)={\frac {f(x)}{g(x)}}}, where both f and g are differentiable and {\displaystyle g(x)\neq 0.} The quotient rule states that the derivative of h(x) is

{\displaystyle h'(x)={\frac {f'(x)g(x)-f(x)g'(x)}{(g(x))^{2}}}.}

It is provable in many ways by using other derivative rules.

Example 1: Basic example

[edit]

Given {\displaystyle h(x)={\frac {e^{x}}{x^{2}}}}, let {\displaystyle f(x)=e^{x},g(x)=x^{2}}, then using the quotient rule:{\displaystyle {\begin{aligned}{\frac {d}{dx}}\left({\frac {e^{x}}{x^{2}}}\right)&={\frac {\left({\frac {d}{dx}}e^{x}\right)(x^{2})-(e^{x})\left({\frac {d}{dx}}x^{2}\right)}{(x^{2})^{2}}}\\&={\frac {(e^{x})(x^{2})-(e^{x})(2x)}{x^{4}}}\\&={\frac {x^{2}e^{x}-2xe^{x}}{x^{4}}}\\&={\frac {xe^{x}-2e^{x}}{x^{3}}}\\&={\frac {e^{x}(x-2)}{x^{3}}}.\end{aligned}}}

Example 2: Derivative of tangent function

[edit]

The quotient rule can be used to find the derivative of {\displaystyle \tan x={\frac {\sin x}{\cos x}}} as follows: {\displaystyle {\begin{aligned}{\frac {d}{dx}}\tan x&={\frac {d}{dx}}\left({\frac {\sin x}{\cos x}}\right)\\&={\frac {\left({\frac {d}{dx}}\sin x\right)(\cos x)-(\sin x)\left({\frac {d}{dx}}\cos x\right)}{\cos ^{2}x}}\\&={\frac {(\cos x)(\cos x)-(\sin x)(-\sin x)}{\cos ^{2}x}}\\&={\frac {\cos ^{2}x+\sin ^{2}x}{\cos ^{2}x}}\\&={\frac {1}{\cos ^{2}x}}=\sec ^{2}x.\end{aligned}}}

The reciprocal rule is a special case of the quotient rule in which the numerator {\displaystyle f(x)=1}. Applying the quotient rule gives{\displaystyle h'(x)={\frac {d}{dx}}\left[{\frac {1}{g(x)}}\right]={\frac {0\cdot g(x)-1\cdot g'(x)}{g(x)^{2}}}={\frac {-g'(x)}{g(x)^{2}}}.}

Utilizing the chain rule yields the same result.

Proof from derivative definition and limit properties

[edit]

Let {\displaystyle h(x)={\frac {f(x)}{g(x)}}.} Applying the definition of the derivative and properties of limits gives the following proof, with the term {\displaystyle f(x)g(x)} added and subtracted to allow splitting and factoring in subsequent steps without affecting the value:{\displaystyle {\begin{aligned}h'(x)&=\lim _{k\to 0}{\frac {h(x+k)-h(x)}{k}}\\&=\lim _{k\to 0}{\frac {{\frac {f(x+k)}{g(x+k)}}-{\frac {f(x)}{g(x)}}}{k}}\\&=\lim _{k\to 0}{\frac {f(x+k)g(x)-f(x)g(x+k)}{k\cdot g(x)g(x+k)}}\\&=\lim _{k\to 0}{\frac {f(x+k)g(x)-f(x)g(x+k)}{k}}\cdot \lim _{k\to 0}{\frac {1}{g(x)g(x+k)}}\\&=\lim _{k\to 0}\left[{\frac {f(x+k)g(x)-f(x)g(x)+f(x)g(x)-f(x)g(x+k)}{k}}\right]\cdot {\frac {1}{[g(x)]^{2}}}\\&=\left[\lim _{k\to 0}{\frac {f(x+k)g(x)-f(x)g(x)}{k}}-\lim _{k\to 0}{\frac {f(x)g(x+k)-f(x)g(x)}{k}}\right]\cdot {\frac {1}{[g(x)]^{2}}}\\&=\left[\lim _{k\to 0}{\frac {f(x+k)-f(x)}{k}}\cdot g(x)-f(x)\cdot \lim _{k\to 0}{\frac {g(x+k)-g(x)}{k}}\right]\cdot {\frac {1}{[g(x)]^{2}}}\\&={\frac {f'(x)g(x)-f(x)g'(x)}{[g(x)]^{2}}}.\end{aligned}}}The limit evaluation {\displaystyle \lim _{k\to 0}{\frac {1}{g(x+k)g(x)}}={\frac {1}{[g(x)]^{2}}}} is justified by the differentiability of {\displaystyle g(x)}, implying continuity, which can be expressed as {\displaystyle \lim _{k\to 0}g(x+k)=g(x)}.

Proof using implicit differentiation

[edit]

Let {\displaystyle h(x)={\frac {f(x)}{g(x)}},} so that {\displaystyle f(x)=g(x)h(x).}

The product rule then gives {\displaystyle f'(x)=g'(x)h(x)+g(x)h'(x).}

Solving for {\displaystyle h'(x)} and substituting back for {\displaystyle h(x)} gives: {\displaystyle {\begin{aligned}h'(x)&={\frac {f'(x)-g'(x)h(x)}{g(x)}}\\&={\frac {f'(x)-g'(x)\cdot {\frac {f(x)}{g(x)}}}{g(x)}}\\&={\frac {f'(x)g(x)-f(x)g'(x)}{[g(x)]^{2}}}.\end{aligned}}}

Proof using the reciprocal rule or chain rule

[edit]

Let {\displaystyle h(x)={\frac {f(x)}{g(x)}}=f(x)\cdot {\frac {1}{g(x)}}.}

Then the product rule gives {\displaystyle h'(x)=f'(x)\cdot {\frac {1}{g(x)}}+f(x)\cdot {\frac {d}{dx}}\left[{\frac {1}{g(x)}}\right].}

To evaluate the derivative in the second term, apply the reciprocal rule, or the power rule along with the chain rule: {\displaystyle {\frac {d}{dx}}\left[{\frac {1}{g(x)}}\right]=-{\frac {1}{g(x)^{2}}}\cdot g'(x)={\frac {-g'(x)}{g(x)^{2}}}.}

Substituting the result into the expression gives{\displaystyle {\begin{aligned}h'(x)&=f'(x)\cdot {\frac {1}{g(x)}}+f(x)\cdot \left[{\frac {-g'(x)}{g(x)^{2}}}\right]\\&={\frac {f'(x)}{g(x)}}-{\frac {f(x)g'(x)}{g(x)^{2}}}\\&={\frac {g(x)}{g(x)}}\cdot {\frac {f'(x)}{g(x)}}-{\frac {f(x)g'(x)}{g(x)^{2}}}\\&={\frac {f'(x)g(x)-f(x)g'(x)}{g(x)^{2}}}.\end{aligned}}}

Proof by logarithmic differentiation

[edit]

Let {\displaystyle h(x)={\frac {f(x)}{g(x)}}.} Taking the absolute value and natural logarithm of both sides of the equation gives {\displaystyle \ln |h(x)|=\ln \left|{\frac {f(x)}{g(x)}}\right|}

Applying properties of the absolute value and logarithms, {\displaystyle \ln |h(x)|=\ln |f(x)|-\ln |g(x)|}

Taking the logarithmic derivative of both sides, {\displaystyle {\frac {h'(x)}{h(x)}}={\frac {f'(x)}{f(x)}}-{\frac {g'(x)}{g(x)}}}

Solving for {\displaystyle h'(x)} and substituting back {\displaystyle {\tfrac {f(x)}{g(x)}}} for {\displaystyle h(x)} gives: {\displaystyle {\begin{aligned}h'(x)&=h(x)\left[{\frac {f'(x)}{f(x)}}-{\frac {g'(x)}{g(x)}}\right]\\&={\frac {f(x)}{g(x)}}\left[{\frac {f'(x)}{f(x)}}-{\frac {g'(x)}{g(x)}}\right]\\&={\frac {f'(x)}{g(x)}}-{\frac {f(x)g'(x)}{g(x)^{2}}}\\&={\frac {f'(x)g(x)-f(x)g'(x)}{g(x)^{2}}}.\end{aligned}}}

Taking the absolute value of the functions is necessary for the logarithmic differentiation of functions that may have negative values, as logarithms are only real-valued for positive arguments. This works because {\displaystyle {\tfrac {d}{dx}}(\ln |u|)={\tfrac {u'}{u}}}, which justifies taking the absolute value of the functions for logarithmic differentiation.

Higher order derivatives

[edit]

Implicit differentiation can be used to compute the nth derivative of a quotient (partially in terms of its first n − 1 derivatives). For example, differentiating {\displaystyle f=gh} twice (resulting in {\displaystyle f''=g''h+2g'h'+gh''}) and then solving for {\displaystyle h''} yields{\displaystyle h''=\left({\frac {f}{g}}\right)''={\frac {f''-g''h-2g'h'}{g}}.}